Design of Azomethine Diols for Efficient Self-Healing of Strong Polyurethane Elastomers - Dae-Woo Lee; Han-Na Kim; Dai-Soo Lee (Molecules, 2018)
Azomethine diols (AMDs) were synthesized by condensation between a terephthalic aldehyde, polyether diamine, and ethanol amine. The synthesized AMDs were employed to introduce azomethine groups into the backbones of polyurethane elastomers (PUEs). Different AMDs were designed to control the concentration and distribution of azomethine groups in PUEs. In this study, we explored the intrinsic self-healing of AMD-based PUEs by azomethine metathesis. Particularly, the effects of the concentration and distribution of the azomethine groups on the AMD-based PUEs were considered. Consequently, as the azomethine group concentration increased and the distribution became denser, the self-healing properties improved. With AMD3-40, the self-healing efficiency reached 86% at 130 °C after 30 min. This represents a 150% improvement over the control PUE. Additionally, as the AMD content increased, the mechanical properties improved. With AMD3-40, the tensile strength reached 50 MPa. Therefore, we concluded that the self-healing and mechanical properties of PUEs can potentially be tailored for applications by adjusting the concentration and design of AMD structure for PUEs.